2017
DOI: 10.1080/07434618.2017.1373855
|View full text |Cite
|
Sign up to set email alerts
|

High-technology augmentative and alternative communication for individuals with intellectual and developmental disabilities and complex communication needs: a meta-analysis

Abstract: The use of mobile technology is ubiquitous in modern society and is rapidly increasing in novel use. The use of mobile devices and software applications ("apps") as augmentative and alternative communication (AAC) is rapidly expanding in the community, and this is also reflected in the research literature. This article reports the social-communication outcome results of a meta-analysis of single-case experimental research on the use of high-tech AAC, including mobile devices, by individuals with intellectual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 72 publications
8
70
1
2
Order By: Relevance
“…In a recent meta-analysis of these interventions towards individuals with ID, authors reported their efficacy to improve communication of this population [8]. Authors also argued that such good results can be observed in protected environments but also in mainstream environments, therefore suggesting that providing support in situ may promote generalization of learnings.…”
Section: Alternative and Augmentative Communication (Aac) Supportsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent meta-analysis of these interventions towards individuals with ID, authors reported their efficacy to improve communication of this population [8]. Authors also argued that such good results can be observed in protected environments but also in mainstream environments, therefore suggesting that providing support in situ may promote generalization of learnings.…”
Section: Alternative and Augmentative Communication (Aac) Supportsmentioning
confidence: 99%
“…In the same vein, the lack of measures related to social validity (only 2 on 15 reviewed studies) questions both the feasibility and relevance of such interventions in real-life situations [9]. Moreover, literature mostly investigated the effects of these interventions on children with ID, and data addressing adults with ID are very communication interventions focus almost exclusively on developing basic requests skills, and urge to go beyond to develop other communication aspects [8][9]. In that sense, AAC tools often offer "basic" features only allowing selecting a pictogram and its vocalization [11][12].…”
Section: Limits Of Existing Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…SGDs range from mid-tech battery-operated SGDs to high-tech computerized SGDs with synthetic or digitalized speech (Myrden, Schudlo, Weyand, Zeyl, & Chau, 2014). SGDs give individuals with severe communication impairments a voice and enable their participation in education, in faceto-face communication, and in communication over a distance (Caron & Light, 2016;Ganz et al, 2017;Holmqvist, Thunberg, & Peny Dahlstrand, 2017). SGDs can be directly accessed with selection aids such as pointing, trackballs, joysticks, and contacts, or by eye gaze technology.…”
Section: Introductionmentioning
confidence: 99%